1996
DOI: 10.1037/0021-9010.81.6.827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transformational leadership training on attitudinal and financial outcomes: A field experiment.

Abstract: A pretest-posttest control-group design (N = 20) was used to assess the effects of transformational leadership training, with 9 and 11 managers assigned randomly to training and control groups, respectively. Training consisted of a 1-day group session and 4 individual booster sessions thereafter on a monthly basis. Multivariate analyses of covariance, with pretest scores as the covariate, showed that the training resulted in significant effects on subordinates' perceptions of leaders' transformational leadersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
805
2
17

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 958 publications
(861 citation statements)
references
References 26 publications
37
805
2
17
Order By: Relevance
“…Through empowerment programs organizations may set the stage for the more effective use of transformational leadership in engendering innovative behavior. Furthermore, research has shown that transformational and transactional leadership can be learned and training programs have been developed (Barling, Weber, & Kelloway, 1996;Dvir, Eden, Avolio, & Shamir, 2002), suggesting that efforts to increase follower psychological empowerment can be complemented by leadership development efforts to increase transformational leadership.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Through empowerment programs organizations may set the stage for the more effective use of transformational leadership in engendering innovative behavior. Furthermore, research has shown that transformational and transactional leadership can be learned and training programs have been developed (Barling, Weber, & Kelloway, 1996;Dvir, Eden, Avolio, & Shamir, 2002), suggesting that efforts to increase follower psychological empowerment can be complemented by leadership development efforts to increase transformational leadership.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Transformational leaders can motivate followers to reach their fullest potential and exceed expected performance, as well as increasing their level of satisfaction and commitment to the organization [10,11]. Compared with transactional leadership, transformational leadership is believed to be advantageous in developing leaders and improving followers" loyalty, trust, self-esteem and self-efficacy [12,13].…”
Section: I. Introductionmentioning
confidence: 99%
“…Specifically, Bass [6] described transformational leadership as leader behaviors that stimulate and inspire followers to achieve extraordinary outcomes by raising the level of motivation and morality in both themselves and their followers. Transformational leaders are effective in promoting organizational commitment by aligning goals and values of the follower, the group, the leader, and the organization [10,12,21]. Its strong, positive effects on followers" attributes and commitment will then motivate followers to reach their fullest potential and exceed expected performance [11].…”
Section: I. Introductionmentioning
confidence: 99%
“…Dvir et al (2002) demonstrated a positive impact of transformational leadership training in the Israeli army on follower self-efficacy, extra effort, critical-independent approach, and objective performance. Barling et al (1996), in a sample of Canadian bank employees, found significant improvements in commitment and performance among followers whose leaders had attended a transformational leadership training program.…”
Section: Leadership and Organizational Learningmentioning
confidence: 99%
“…Most studies have focused on transformational leadership training, demonstrating that such training can increase not only employees perception of leaders' transformational leadership (Barling et al, 1996, Kelloway et al, 2000, Duygulu and Kublay, 2011, Brown and May, 2012, Fitzgerald and Schutte, 2010 but also their attitudes and behaviors. For example, Hardy et al (2010) found that transformational leadership training in the British army increased employees' selfconfidence and resilience.…”
Section: Leadership and Organizational Learningmentioning
confidence: 99%